Relationship of Motivation and Supervision with Nurse Performance in Implementing Nursing Care - Delima, Mera; Dioso, Regidor III; Aljaberi, Musheer Abdulwahid; Anggreiniboti, Tanti; Raymond, Jessica; Devitra, Anferi; Elghannam, Tarek Ahmed (Qualitative and Quantitative Research Center, 2024)
The performance of nurses in delivering optimal nursing care is critical to achieving quality healthcare outcomes. Motivation and supervision are key factors influencing their effectiveness. Understanding the interplay between these elements provides valuable insights into improving nursing care quality, fostering professional growth, and enhancing patient satisfaction within healthcare settings. This study investigates the relationship between motivation and supervision with nurse performance in implementing nursing care. The method used a descriptive correlation design with a cross-sectional approach; data were collected from 50 respondents selected through purposive sampling. The respondent was Irma A. inpatient room located at Sungai Dareh Hospital. Motivation, supervision, and nurse performance were measured using questionnaires, and data were analysed with the Spearman Rank test. The results revealed that most nurses exhibited moderate motivation levels (92%) and were under moderate supervision (100%). A significant relationship was found between motivation and nurse performance (p = 0.009, r = 0.368) and between supervision and nurse performance (p = 0.000, r = 0.499). These findings highlight the critical role of motivation and supervision in enhancing nurse performance. Adequate motivation fosters enthusiasm and productivity, while effective supervision provides essential guidance and support to achieve optimal care standards. This study underscores the need for sustainable programs to enhance motivation and supervision quality, aiming to improve nurse performance and the overall quality of nursing care in health facilities. The study’s contribution to nursing management and performance enhancement is significant, and its suggestions for improving motivation and supervision are valuable for healthcare institutions.